News and Analysis : US federal court slaps open-access publisher with 50m fine. (4th June 2019) - Allen, Michael
Abstract: The open-access publisher OMICS Group has been ordered to pay 50.1m in damages by a US federal court for misrepresenting its publications, hiding publication fees and making misleading claims about its conferences.